2012
DOI: 10.1007/s10165-012-0650-9
|View full text |Cite
|
Sign up to set email alerts
|

A case of adult-onset Still’s disease complicated by thrombotic thrombocytopenic purpura with retinal microangiopathy and rapidly fatal cerebral edema

Abstract: We present a patient who had adult-onset Still's disease (AOSD) complicated by thrombotic thrombocytopenic purpura (TTP) that resulted in retinal microangiopathy and rapidly fatal cerebral edema. The patient was a 37-year-old male who developed fever, eruption, arthritis and hepatic dysfunction, that, based on close examination, was diagnosed as AOSD. Despite treatment with corticosteroids, the patient developed acute visual field defect, neurological deterioration including convulsions and impaired consciousn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…An early sign that should raise the index of suspicion for TTP is development of acute vision impairment. In extreme cases, multiple thrombi formation and massive cytokine release causing progressive vascular permeability, worsening brain edema and, ultimately, rapid death may also occur [53].…”
Section: Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%
See 1 more Smart Citation
“…An early sign that should raise the index of suspicion for TTP is development of acute vision impairment. In extreme cases, multiple thrombi formation and massive cytokine release causing progressive vascular permeability, worsening brain edema and, ultimately, rapid death may also occur [53].…”
Section: Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%
“…There have been at least 11 published cases of TTP/HUS associated with AOSD, five of which with presenting renal failure [56]. Masuyama et al reported a case of AOSD complicated by TTP that resulted in retinal microangiopathy and rapidly fatal cerebral edema [53].…”
Section: Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%
“…The association of AOSD with TMA is rare, and to our knowledge, fewer than 30 cases have been reported in the English literature (78,(80)(81)(82)(83). In most cases, TMA occurred during an AOSD flare, and AOSD treatment was associated with TMA resolution, which argues for a pathophysiological link between AOSD and TMA (78).…”
Section: Thrombotic Microangiopathymentioning
confidence: 99%
“…Supportive care in an ICU, with plasma exchange being central [75] 2. High-dose steroids intravenously and then orally Other immunomodulatory agents proposed for refractory cases include anakinra [74], tocilizumab [76], intravenous immunoglobulins, cyclophosphamide, azathioprine, cyclosporine A, and rituximab [60,74]. Despite this treatment, mortality associated with TMA remains high, up to 20% [60].…”
Section: Coagulation Disordersmentioning
confidence: 99%